Kids or courses? Gender differences in the effects of active labor market policies - Michael Lechner; Stephan Wiehler (Institute for the Study of Labor (IZA), 2007)
This paper investigates active labor market programs in Austria with a special emphasis on male-female effect heterogeneity. On average, we find only small effects, if any, for most of the programs. A crucial advantage of the large and informative administrative data we use is that it provides records about pregnancies and times of parental leave, in addition to the information that can typically be found in European administrative data sources used for evaluating active labor market policies. We show that these variables play a key role in removing selection bias and defining outcome variables which may explain why other similar studies found such programs to be more effective for women than for men. In particular for younger women a key effect of the programs is to reduce or postpone pregnancies and to increase the attachment to the labor force. After taking into account gender specific selection effects and the effects of the programs on pregnancies, gender differences (almost) disappear.
urn:nbn:de:101:1-20080402347
Keywords: 330; Arbeitsmarktpolitik; Wirkungsanalyse; Männer; Frauen; Mutterschutz; Schwangerschaft; Österreich